Diagnosis klinis infeksi herpes zoster (laporan kasus)Clinic diagnosis of herpes zoster (case report) - M. Jusri; Erni Marlina (DiscoverSys Inc., 2011)
Varicella is the fastest spreading infection. This virus classified as DNA virus with primer infection that causedchicken pox mainly seen in children. Reactivation of this infection causes herpes zoster or shingle. Painfull of areainvolved proceed the unilateral and segmental nature of disease. If facial involved segmentally, it occurs painespecially at the facial and dentition that sometimes suspect as pulpitis. This case report is aimed to discussdiagnosis and management of herpes zoster with headache. Patient, male, 66 years old came with chief complaint ofheadache and ulcers on right facial with eat disturbance due to oral cavity pain. The diagnosis was herpes zoster.Patient was prescribed with acyclovir 1600 mg 4 times per day, analgesic, antibiotic mouth wash, and vitamins.Oral pain disappeared in 3 days, dan after 3 weeks healed completely. Diagnosis of herpes zoster could be get fromdetail anamnesis and examination.